FACTORS ASSOCIATED WITH VOICE DISORDERS: A SYSTEMATIC REVIEW - Monica, Desnita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: During the ageing process, the larynx and structures involved in phonation undergo natural changes that account for the distinctive characteristics of geriatric voices. A voice disorder has occurred when, at any time, a person's voice fails and causes communication difficulties. This can have an adverse effect on communicative efficacy and quality of life, compromising mechanisms of socialisation, the maintenance of autonomy, and the feeling of well-being. However, there appears to be a lack of clarity regarding the factors associated with voice disorders in this population, particularly from an epidemiological standpoint.Objective: This study aims to identify factors associated with voice disorders in elderly through a comprehensive systematic review.Methods: A systematic review of literature published between 2004 and July 2023 was performed across several databases including MEDLINE/PubMed, Cochrane Library, and Google Scholar. Duplicate publications, review articles, and incomplete articles were excluded.Results: We included four appropriate studies in this systematic review, involving 65.112 patients in total. The population of the study was elderly, aged 60 years and older. The factors associated with voice disorders include, but are not limited to, age, gender, comorbid conditions such as colds, sore throats, gastroesophageal reflux, arthritis, thyroid problems, bronchitis, sleep disorders, asthma, chronic obstructive pulmonary disease, vocal fold disease, depression or anxiety, and geographic locations.Conclusion: Physical and psychosocial factors were associated with voice disorders in the elderly. However, the methodological differences between the studies included in this review, particularly in terms of sample selection and the instruments used, indicate a great deal of variability and undermine the results' reliability.